Detection of Pneumocystis carinii in respiratory specimens by PCR-solution hybridization enzyme-linked immunoassay. - Ortona, E (1997)
By using a recently developed PCR-solution hybridization enzyme-linked assay (PCR-SHELA), we investigated Pneumocystis carinii in bronchoalveolar lavage fluid samples and induced sputa of patients with pneumocystosis. In detecting P. carinii, PCR-SHELA proved more sensitive than immunofluorescence staining or a single PCR and significantly more diagnostically specific than a nested PCR. Our data suggest that PCR-SHELA could be used to detect P. carinii organisms in respiratory samples, particularly in patients with uncertain diagnoses.